2007
DOI: 10.1111/j.1399-3054.2007.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of photosynthesis and functions of the water–water cycle in rice (Oryza sativa) leaves in response to potassium deficiency

Abstract: The mechanisms of photoprotection of photosynthesis and dissipation of excitation energy in rice leaves in response to potassium (K) deficiency were investigated. Net photosynthetic rate and the activity of ribulose-1,5-bisphosphate carboxylase/oxygenase decreased under K deficiency. Compared with the control, non-photochemical quenching of Chl fluorescence increased in K-deficient plant, whereas the efficiency of excitation transfer (F'(v)/F'(m)) and the photochemical quenching coefficient (q(P)) decreased. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 31 publications
7
43
1
2
Order By: Relevance
“…This is confirmed by the reduction in CO 2 assimilation rate and in F PSII . Similar results have been reported by other authors in Oryza sativa leaves in response to K deficiency (Weng et al, 2007).…”
Section: Article In Presssupporting
confidence: 91%
“…This is confirmed by the reduction in CO 2 assimilation rate and in F PSII . Similar results have been reported by other authors in Oryza sativa leaves in response to K deficiency (Weng et al, 2007).…”
Section: Article In Presssupporting
confidence: 91%
“…The water-water cycle is inevitably coupled with the generation of ROS such as O 2 -and H 2 O 2 (Asada, 1999), which would potentially cause photooxidative damage on the thylakoid membrane and stroma proteins. The limiting step of the water-water cycle is the photoreduction of O 2 to O 2 - (Endo and Asada, 2006), and both SOD and APX are key enzymes involved in ROS scavenging (Weng et al, 2007). In our study, it was found that in the two cultivars the increased J a was accompanied by enhanced activity of SOD under N-deficiency (Figs.…”
Section: Discussionsupporting
confidence: 53%
“…2C, 3A). Similarly, in rice plants the increase in J a accompanying with enhancement of O 2 -production rate and SOD activity was observed in response to potassium deficiency (Weng et al, 2007) and phosphorus defi ciency (Weng et al, 2008). Since SOD is present in mitochondria as well as chloroplasts, it can be speculated that high SOD activity under the LN condition may be related not only to increased rate of photoreduction of oxygen in chloroplasts, but also to a rise in respiration and the subsequent scavenging of reduced ROS in the mitochondria.…”
Section: Discussionmentioning
confidence: 94%
“…DW reduction may be the consequence of a reduction in photosynthesis per leaf unit area (Bednarz and Oosterhuis 1999;Zhao et al 2001;Jordan-Meille and Pellerin 2008;Pettigrew 2008). Three major causes of a reduction of photosynthesis under K deficiency have been implicated: (i) reduced stomatal and mesophyll conductance (Terry and Ulrich 1973;Longstreth and Nobel 1980;Pervez et al 2004): (ii) a negative feedback on CO 2 assimilation rates induced by the accumulation of soluble sugars Roitsch 1999) which can impact negatively on the activity of the enzyme Rubisco (Farquhar et al 1980); (iii) impaired counterbalancing by K + of H + accumulation during electron transport across the thylakoid membrane (Mengel 1984;Tester and Blatt 1989;Weng et al 2007). The photosynthetic model proposed by Farquhar and Sharkey (1982) is appropriate to quantify among these three mechanisms which ones are affected by K-deficiency.…”
Section: Introductionmentioning
confidence: 97%